2018
DOI: 10.3390/en11113135
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Study of a Rooftop Vertical Axis Wind Turbine Tower Based on an Automated Vibration Data Processing Algorithm

Abstract: When constructed on tall building rooftops, the vertical axis wind turbine (VAWT) has the potential of power generation in highly urbanized areas. In this paper, the ambient dynamic responses of a rooftop VAWT were investigated. The dynamic analysis was based on ambient measurements of the structural vibration of the VAWT (including the supporting structure), which resides on the top of a 24-story building. To help process the ambient vibration data, an automated algorithm based on stochastic subspace identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Similar results are achieved in [14]. In [15], a test case rooftop VAWT similar to the one in the present work is considered: a health monitoring system is implemented and the dynamic behavior of the VAWT is studied using vibration measurements under ambient conditions. To process the vibration data, an automated algorithm based on stochastic subspace identification (SSI) and a fast clustering approach is developed and presented to show how modes could be determined: one of the main result of the study is that the modal behaviors can be differentiated into building-associated and non-building-associated modes.…”
Section: Introductionsupporting
confidence: 65%
“…Similar results are achieved in [14]. In [15], a test case rooftop VAWT similar to the one in the present work is considered: a health monitoring system is implemented and the dynamic behavior of the VAWT is studied using vibration measurements under ambient conditions. To process the vibration data, an automated algorithm based on stochastic subspace identification (SSI) and a fast clustering approach is developed and presented to show how modes could be determined: one of the main result of the study is that the modal behaviors can be differentiated into building-associated and non-building-associated modes.…”
Section: Introductionsupporting
confidence: 65%
“…Another study was performed on the rooftop of 24 story building [33]. The result showed that building vibration contributed to the vibration of the VAWT tower, not the other way around.…”
Section: Energy Potential Production For Multiple Turbinesmentioning
confidence: 99%
“…Vertical axis wind turbines can mainly be divided into Darrieus type, Savonius type, and Giromill type . Among them, the Darrieus‐type wind turbines can convert the highest amount of energy due to a higher tip‐speed ratio . The straight‐bladed VAWTs developed from traditional Darrieus‐type wind turbines have simple blade shapes and wind wheel structures, which are convenient to design and install.…”
Section: Introductionmentioning
confidence: 99%
“…Several laboratory vibration tests were conducted to study the dynamic behavior of VAWTs. Wang et al investigated the ambient dynamic responses of a rooftop VAWT and found that the wind direction has little effect on its vibration amplitude. Mclaren et al showed that the vibration of the VAWT support tower may be influenced by the wind turbine's operation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation